Preliminary Research: Development of A Teaching Module Based on Problem Based Learning To Improve Students' Mathematical Literacy Abilities - Lestari, Nur Puji (Universitas Wiralodra, 2023)
Mathematical literacy plays an important role in life. It can be used by humans in solving everyday life problems. However student’s mathematical literacy ability are still very low. Therefore mathematics learning needs to be oriented to enhancing mathematical literacy ability. Mathematics learning will run smoothly if accompanied by good planning. This study aims to develop teaching module based on problem based learning. This research uses Research and Development method with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) stages. In this preliminary research we carry out the analyze and design stages. At the analyze stage the data is processed using a qualitative descriptive approach and it is known that Three Variables Linear Equation System (TVLES) is difficult material for student. This is caused by limited teaching material and learning is not linked to contextual problems. Based on the results of the mathematical literacy test, it is known that student’s mathematical literacy ability are very low, only 6% student are able to reach minimum criteria of 75. So this research can be continued by developing teaching modules based on problem based learning to enhance student’s mathematical literacy ability.